Dari Partisipasi Menuju Pelestarian: Peran Komunitas dalam Konservasi Cagar Budaya Candi Pringtali, Kulon Progo, 1988-2019 - Apriatama, Dani; Subaryana, Subaryana; Lestari, Siska Nurazizah (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
Cultural heritage comprises tangible assets, both terrestrial and aquatic, that are deeply connected to the cultural and historical development of human civilization. This study explores the historical narrative of Pringtali Temple in Kulon Progo Regency, the role of the Pringtali Hamlet community in its preservation from 1988 to 2019, and the management, revitalization, and official designation process of the temple as a Cultural Heritage Site in 2019. Employing a historical research method, the study follows four key stages: heuristics, source criticism, interpretation, and historiography. The findings indicate that the Pringtali community played a pivotal role in preserving the temple—beginning with the reporting of the temple’s collapse in 1944, rediscovering the buried Sendang Pringtali spring in 2017, maintaining the annual clean water tradition, and promoting the temple's existence. The designation process involved establishing a formal management structure, revitalizing the temple area, submitting a recommendation manuscript on August 8, 2019, and achieving official heritage status on 12 December 2019. The study concludes that sustained community participation was a critical factor in the temple’s recognition as cultural heritage, contributing to its preservation, aesthetic improvement, and structural conservation.